Jumanca, Romanița, Characteristics of the English and Romanian Legal Discourse. A Comparative Approach. Szeged: JATE Press, ISBN: 9789633153734, pp.401 - Alexandru ORAVIȚAN (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2020)
Book review